Centro Integrado de Educación de Adultos (CINDEA): An educational modality that achieves goals in technical instruction in Costa Rica - Cruz Villalobos, Marianela (2024)
This essay discusses how the Centros Integrados de Educación de Adultos (CINDEA) collaborate to break educational barriers in technical training in Costa Rica and how these institutions are a bridge between formal education and the labor market, by providing people with the possibility of developing skills valued in the professional environment.  The objective of this essay is to socialize the work dynamics employed in this modality and to expose how it promotes equal opportunities by allowing all people over 15 years of age, without exception, to develop knowledge related to a technical area.  It also discusses the challenges they face that, in many cases, hinder their important work in Costa Rican education.